The possibility of harmonizing the recombinant erythropoietin specific activity determination method with European Pharmacopoeia - A. K. Yakovlev; L. A. Gayderova; V. N. Podkuiko; R. A. Volkova; N. A. Alpatova; Yu. V. Olefir (Стандартные образцы)
Rationale. The task of import substitution in health care and the development of normative legal acts in the framework of the Eurasian Economic Community raises the questions of harmonization of national requirements with international ones, including the standardization of drugs. Thereby, the assessment of the quality of domestic recombinant human erythropoietin in accordance with European Pharmacopoeia requirements is very actual. The main indicator of drug quality is specific activity of drug (rhepo). In Russian Federation it is determined by the influence of the drug on erythropoiesis stimulation. This effect of erythropoietin is measured by counting the number of reticulocytes using the flow cytometry and light microscopy. The latter method of calculation is not included in European Pharmacopoeia. Adequate assessment of this indicator is required for the development of national requirements for quality control of drugs rhepo harmonized with European Pharmacopoeia. Purpose of the work. The study aimed the comparative evaluation of the accuracy of the specific erythropoietin activity determination method using the flow cytometry and light microscopy data to provide the harmonization of the draft General monograph with European Pharmacopoeia. Research methods. The erythropoietin specific activity was determined in vivo in normocythaemic mice using the flow cytometry in accordance with the European Pharmacopoeia and light microscopy. We have compared the effects of two independent dilution series of erythropoietin European Pharmacopoeia standard sample. Results. The results of specific erythropoietin activity determination obtained by two different methods of measurement differed in the offset from the reference value (certified value). In flow cytometry data, the offset varied between 1-8%, the results of light microscopy showed higher variability ranging from 4 to 31%. The estimation of intermediate precision showed twice lower dispersion of specific erythropoietin activity measurements obtained by flow cytometry in comparison with light immersion microscopy data. Conclusion. Specific erythropoietin drug activity determination with flow cytometry is characterized by high accuracy and meets the European Pharmacopoeia requirements. We have considered the possibility of light microscopy usage for the same task in the absence of a flow cytometer. The usage of light microscopy requires increasing its accuracy in order to harmonize the method with European Pharmacopoeia requirements.